Dengue in the State of Rio Grande do Norte, Brazil, 2010–2012. Issue 12 (19th October 2015) - Branco, Mário S. D.; Sousa, Denise M. C.; Sousa, Daíse M. C.; Monteiro, Joelma D.; Costa, Diego M. P.; Almeida Junior, Renato F.; Lima, Tábata L. C.; Farias, Kleber J. S.; Medeiros, Ralfo C.; Queiroz, Maria Goretti L.; Gil, Laura H. V. G.; Fernandes, José V.; et al.
Abstract: Objective: To present results of virological surveillance and epidemiological aspects of dengue in the State of Rio Grande do Norte, Brazil. Methods: A total of 1581 cases, reported from 2010 to 2012 at various health centres in the state, were analysed by viral isolation and/or RT‐PCR for viral detection and typing. To identify whether different genotypes were circulating in the state during this period, sequencing of the complete E gene for DENV (1485 bp in length) was performed directly from patient serum samples. Results: All four serotypes of dengue virus circulated in Rio Grande do Norte, with the introduction of DENV‐4 in the state in 2011. In 2012, DENV‐4 represented 100% of positive confirmed cases. 53.97% of cases occurred in Natal. Case numbers peaked in April (21%) and May (23%). Genetic characterisation of circulating strains confirmed the circulation of genotypes V, south‐east Asian/American and II, respectively, for DENV‐1, DENV‐2 and DENV‐4. Conclusions: This work furthers a better understanding of dengue viruses in the State of Rio Grande do Norte. Strengthening control efforts in the region is important considering the impact of dengue.